2008
DOI: 10.1523/jneurosci.0473-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Dopamine Release Associated with a Human Dopamine Transporter Coding Variant

Abstract: Dopamine (DA) signaling at synapses is tightly coordinated through opposing mechanisms of vesicular fusion-mediated DA release and transporter-mediated DA clearance. Altered brain DA signaling is suspected to underlie multiple brain disorders, including schizophrenia, Parkinson's disease, bipolar disorder, and attention-deficit hyperactivity disorder (ADHD). We identified a pedigree containing two male children diagnosed with ADHD who share a rare human DA transporter (DAT; SLC6A3) coding variant, Ala559Val. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
164
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(178 citation statements)
references
References 31 publications
14
164
0
Order By: Relevance
“…As noted in the prior publication, these mice reproduce normally and display no overt sensorimotor deficits. Our previous heterologous expression studies demonstrated no impact of the DAT Val559 substitution on total or cell surface expression, inward DA transport, or sensitivity to psychostimulants (8,58). Consistent with these findings, striatal extracts from DAT Val559 animals demonstrate normal transporter protein levels (Fig.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…As noted in the prior publication, these mice reproduce normally and display no overt sensorimotor deficits. Our previous heterologous expression studies demonstrated no impact of the DAT Val559 substitution on total or cell surface expression, inward DA transport, or sensitivity to psychostimulants (8,58). Consistent with these findings, striatal extracts from DAT Val559 animals demonstrate normal transporter protein levels (Fig.…”
Section: Resultssupporting
confidence: 81%
“…The key phenotypes found for DAT Val559 in transfected cells are ADE and a loss of AMPH-induced DA release (13,58). Evidence of ADE in vivo arises from both our striatal microdialysis studies that demonstrate a significant elevation of basal extracellular DA levels and our findings of elevated presynaptic D2 modulation of vesicular DA release that can be normalized with D2R antagonist (raclopride) treatments.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Transporter-expressing cell lines allow the characterization of psychoactive compounds (Tatsumi et al, 1997) and are also a useful tool for discovering psychoactive therapeutic drugs (Bang-Andersen et al, 2011). Furthermore, in vitro experiments with transfected cells formed the basis for many genetic mutations that were later engineered in mice, which now serve for in vivo investigations of psychoactive drugs or as preclinical models of mental disorders (Henry et al, 2006;Mazei-Robison et al, 2008;Prasad et al, 2005). For example, in vitro experiments allowed the construction of a transgenic mouse model with a 5-hydroxytryptamine (5-HT [serotonin]) transporter (SERT) mutation for the in vivo assessment of SERT-mediated effects of antidepressants or cocaine (Prosser et al, 2014;Thompson et al, 2011) or to shed light on functional abnormalities of the DAT variant Val559, which is being investigated as a potential mouse model of attention-deficit hyperactivity disorder (Mergy et al, 2014).…”
Section: Methods For Studying Transporter and Receptor Pharmacology Imentioning
confidence: 99%